The associations between plasma homocysteine, vitamin B12, folate, the Apolipoprotein E genotype and Alzheimer's Disease - Mohamed, Ilhaam (Division of Geriatric Medicine, 2017)
Background: Alzheimer's disease (AD), the commonest form of dementia, affects people in both industrialised and developing countries. Risk factors for the development of AD include age, the presence of the Apolipoprotein ε4 allele, low vitamin B₁₂ and folate levels, and elevated plasma homocysteine concentrations. Most research involving the associations between these risk factors and AD have been conducted in Europe and North America. We know little about AD and its risk factors in a low to middle income country like South Africa, where nutrition is poor and the background population ApoE ε4 allelic frequency is high. Objective: In this prospective observational study, I wished to determine the relationships between plasma homocysteine, vitamin B₁₂, folate, ApoE ε4 status and cognition in a sample of older persons from the greater Cape Town metropolitan area of the Western Cape region of South Africa. Methods: Cognitively healthy controls and AD participants, diagnosed using NINCDS-ADRDA criteria, were recruited from the community. The study had both cross-sectional and longitudinal components. Cross-sectionally, I related non-fasting plasma homocysteine concentrations, vitamin B₁₂ levels, folate concentrations and the ApoE ε4 genotype to scores from a battery of cognitive tests including the Mini Mental State Examination (MMSE), the Cambridge Cognitive Examination (CAMCOG) and the Learning Subscale score of the CAMCOG. In the longitudinal analysis, I tested whether baseline plasma homocysteine concentrations related to cognitive decline one year after the initial assessment. Results: One hundred and thirteen participants were recruited: 60 controls and 53 AD participants. Plasma homocysteine levels increased with age (rs= 0.418, p<0.001) and were inversely related to cognitive scores in all participants. Homocysteine concentrations were inversely related to vitamin B₁₂ and folate in all study participants (vitamin B₁₂rₛ= -0.47, p<0.001, folaterₛ=-0.33, p=0.001). Homocysteine was inversely related to cognition but, in a regression model, this relation was confounded by the effects of age and years of education. Another regression model showed that vitamin B₁₂ and age independently predicted cognitive scores. There were more ApoE ε4 carriers in the AD group compared with controls and ε4 carrier status was significantly associated with AD. The ApoE ε4 allele modified the relationship between homocysteine and cognition. The association between homocysteine and cognition was strong in ApoE ε4 carriers (e.g. MMSE,rₛ=0.33, p=0.003), but absent in ε4 non-carriers. High baseline homocysteine concentrations did not predict cognitive decline 1 year later. Conclusions: These findings, the first from an African low to middle income country, are consistent with those from studies in industrialised countries. Plasma homocysteine levels increased with age and were inversely related to vitamin B₁₂ and folate. The ApoE ε4 allele strengthened the association between homocysteine and cognition, probably through mechanisms that increase neuronal susceptibility to homocysteine toxicity. My study supports the idea that homocysteine-lowering therapy can reduce the risk of developing AD or slow the progression of the disease.